Study on Improvement of Torque Characteristics of IPM BLDC Motor for Electric Water Pump using Ferrite Magnet - Baek, Soo-Whang; ., .; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: The objectives of this study are to propose a design method to replace the permanent magnets of brushless DC (BLDC) motors used in electric water pumps (EWPs) with ferrite materials and to improve the torque characteristics.Methods/Statistical analysis: Using the proposed design algorithm presented in this study, the shape of the ferrite permanent magnet used in the rotor was changed, and the output at the same level was confirmed when compared with that of the conventional model that uses rare-earth magnet. In addition, finite element (FE) analysis verified that the cogging torque and torque-ripple characteristics of the proposed model using a ferrite material improved.Findings: An EWP operated by a BLDC motor is used to improve the engine performance of a vehicle. Applying permanent magnets made of a ferrite material is necessary, which is advantageous in terms of cost in the design of BLDC motors. In particular, ferrite permanent magnets have a good demagnetization characteristic at high temperature compared with rare-earth magnets. By improving the cogging torque and torque ripple of the motor, achieving robust characteristics from disturbance and precisely controlling the system become possible. In this study, BLDC motors for EWPs were designed by replacing the rare-earth permanent magnets with low-cost ferrite permanent magnets. The shape design of the rotor using ferrite permanent magnet was implemented to make the output characteristics of the proposed model conform to the output characteristics of the conventional model, and simultaneously, the cogging torque and torque-ripple characteristics improved. To verify the suitability of the proposed design method, the design results were analyzed using 2D FE-analysis.Improvements/Applications: The proposed design algorithm is suitable for cost reduction and performance improvement of BLDC motors that drive EWPs for automobiles.Â Â
Keywords: Brushless DC; Motor; Ferrite; Cogging Torque; Torque Ripple; Automobile.